Condensin-mediated restriction of retrotransposable elements facilitates brain development in Drosophila melanogaster - Bert I. Crawford; Mary Jo Talley; Joshua Russman; James Riddle; Sabrina Torres; Troy Williams; Michelle S. Longworth (Nature Communications)
Abstract Neural stem and progenitor cell (NSPC) maintenance is essential for ensuring that organisms are born with proper brain volumes and head sizes. Microcephaly is a disorder in which babies are born with significantly smaller head sizes and cortical volumes. Mutations in subunits of the DNA organizing complex condensin have been identified in microcephaly patients. However, the molecular mechanisms by which condensin insufficiency causes microcephaly remain elusive. We previously identified conserved roles for condensins in repression of retrotransposable elements (RTEs). Here, we show that condensin subunit knockdown in NSPCs of the Drosophila larval central brain increases RTE expression and mobility which causes cell death, and significantly decreases adult head sizes and brain volumes. These findings suggest that unrestricted RTE expression and activity may lead to improper brain development in condensin insufficient organisms, and lay the foundation for future exploration of causative roles for RTEs in other microcephaly models.